DEVELOPMENT OF SOCIAL-PSYCHOLOGICAL COMPETENCE IN THE PROCESS OF PROFESSIONAL TRAINING OF FUTURE SPECIALISTS IN SOCIO-ECONOMIC PROFESSIONS (Psychology Travelogs, 2024)
The article is dedicated to the theoretical exploration of the social-psychological competence of future specialists in socio-economic fields during professional training. Through a theoretical analysis of scientific sources, it has been revealed that social-psychological competence is a crucial factor for successful functioning in society, building relationships with others, and achieving personal and professional goals. The assumption is made that the development of social-psychological competence is a factor in the professional development of future specialists in socio-economic professions, contributing to self-actualization and self-realization of higher education seekers.The importance of developing social-psychological competence in the professional training of socio-economic professionals is established. The author argues that this competence is key to interacting with others, fostering effective communication, empathy development, leadership skills, and conflict resolution. The significance of this competence also lies in the ability of professionals to sensitively respond to the needs of others and provide appropriate support.It is clarified that social-psychological competence is a complex phenomenon covering various aspects such as empathy, communication skills, social competence, conflict resolution, assertiveness, adaptability, cultural awareness, and collaboration ability. These components complement each other and assist future professionals in effectively communicating with others, understanding their needs, building positive relationships, and resolving social situations.The author substantiates key factors in the development of social-psychological competence for future professionals in the «person-to-person» sphere during professional training, including emotional-volitional balance, the presence of value orientations, social creativity, the formation of communicative skills, and life satisfaction.
Keywords: social-psychological competence; professionals in socio-economic professions; emotional-volitional sphere; value orientations; social creativity; life satisfaction; communicative skills